MEDIA KERTAS LIPAT SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN SEDERHANA PADA KELAS IV DI MI MURNI SUNAN DRAJAT LAMONGAN - Nailun Najiyyah; Silviana Nur Faizah (Universitas Islam Lamongan, 2019)
Teaching media is a knowledge of the teaching methods used by a teacher or instructor. The method is the method used to achieve the stated goals. Another technique is the presentation technique mastered by the teacher to teach or present learning material to students in the classroom, so that the lesson can be absorbed, understood and utilized by students properly. The better the teaching method, the more effective the achievement of objectives. In reality, the teaching method or method used conveys different information in ways that are used to strengthen students in mastering knowledge, skills and attitudes (cognitive, psychomotor, affective). Specifically the method of teaching in the classroom, the effectiveness of a method is influenced by the goals, student factors, situation factors, and the teacher's own factors. This study aims to determine the effectiveness of the demonstration and recitation methods in increasing student learning motivation in fiqh subjects in class 2 MI. This research is a classroom action research, research instrument using observation sheets and interviews. Data analysis uses a research cycle and is described qualitatively. The results showed an increase in student motivation in fiqh subjects using the method of demonstration and recitation.